Anxiety and depression among cancer patients - Uyen, Nguyen Thi Hong; Quy, Nguyen Do Minh; Thu, Nguyen Thi Dang; Dung, Ho Xuan (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: Depression and anxiety are common problems of cancer patients. They affect importantly the patients’ health, the decision to be treated, and the outcome of the treatment. Objectives: This study aimed to assess the prevalence of depression and anxiety among cancer patients being treated at Hue University Hospital in 2019 and to reveal its correlation factors. Materials and methods: A cross-sectional study was conducted on 104 cancer patients hospitalized for the treatment. Using the CES-DR and GAD-7 scales to assess depression and anxiety disorders. Chisquare Tests and multivariate logistic regression were performed. Results: The rate of depression (CES-DR) and anxiety (GAD-7) was 77.9% and 63.5%, respectively. Multivariate regression analysis showed the correlation of anxiety among cancer patients to stage III, stage IV of cancer, and the presence of difficulty in paying healthcare costs. Whilst, depression had significant associations with gender (female), late stages of cancer (III, IV), and type of cancer (lung cancer, breast cancer, stomach cancer). Conclusions: The prevalence of anxiety and depression was found relatively important in our study among cancer patients. Thus, it is necessary to propose solutions to improve the mental health of cancer patients to increase treatment efficiency.